2023
DOI: 10.1186/s40545-023-00523-6
|View full text |Cite
|
Sign up to set email alerts
|

Community pharmacists’ perceptions and experiences of stress during COVID-19

Abstract: Background Pharmacists play a crucial role in the COVID-19 pandemic scenario, performing frontline roles for the community, and supporting the healthcare system. This study aimed at investigating stress and its correlates among this category of workers at a high risk of SARS-CoV-2 infection. Methods The participants for this study were employees of the “Municipal Pharmaceutical Company” of L’Aquila (Italy). Data were collected using an anonymous, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…At follow-up, the average of the days falls to a value in line with the national average (3.0). The trend observed in this study was similar to that observed in a study with similar instruments in community pharmacists 10 . In particular, the average number of ill-health days was 2.9 in pharmacists and 2.5 in construction workers.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…At follow-up, the average of the days falls to a value in line with the national average (3.0). The trend observed in this study was similar to that observed in a study with similar instruments in community pharmacists 10 . In particular, the average number of ill-health days was 2.9 in pharmacists and 2.5 in construction workers.…”
Section: Discussionsupporting
confidence: 89%
“…The trend observed in this study was similar to that observed in a study with similar instruments in community pharmacists. 10 In particular, the average number of ill-health days was 2.9 in Assessing the Well-being of Construction Workers pharmacists and 2.5 in construction workers. This suggests the need to pay particular attention to a group of workers who more than others need special attention in health protection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the pharmaceutical industry, community pharmacies play a vital role in healthcare delivery and disease prevention [6] , [7] . Community pharmacists are accessible healthcare professionals who are primarily responsible for ensuring the quality of and dispensing medications and ensuring their proper use by dispensing them alongside appropriate information [8] .…”
Section: Introductionmentioning
confidence: 99%